The Migration of Human Follicular Dendritic Cell-Like Cell Is Facilitated by Matrix Metalloproteinase 3 Expression That Is Mediated through TNFα-ERK1/2-AP1 Signaling. (17th June 2021) - Pak, Hyo-Kyung; Kim, Yong-Woo; Nam, Bora; Lee, A-Neum; Roh, Jin; Gil, Minchan; Liu, Chaohong; Chung, Yoo-Sam; Park, Chan-Sik
Abstract : Follicular dendritic cells are important stromal components of the germinal center (GC) and have pivotal roles in maintaining the GC microenvironment for high-affinity antibody production. Tumor necrosis factor- α (TNF α ) is essential for the development and functions of follicular dendritic cells. Despite the importance of follicular dendritic cells in humoral immunity, their molecular control mechanisms have yet to be fully elucidated due to the lack of an adequate investigation system. Here, we have used a unique human primary follicular dendritic cell-like cell (FDCLC) to demonstrate that the migration of these cells is enhanced by TNF α -mediated metalloproteinase 3 (MMP3) expression. MMP3 was found to be highly expressed in normal human GCs and markedly upregulated in human primary FDCLCs by TNF α . TNF α induced ERK1/2 phosphorylation and the transcription of MMP3 through AP1. TNF α treatment increased FDCLC migration, and a knockdown of MMP3 significantly reduced the TNF α -induced migration of FDCLCs. Overall, we have newly identified a control mechanism for the expression of MMP3 in FDCLCs that modulates their migration and may indicate an important role in GC biology. Since GCs are observed in the lesions of autoimmune diseases and lymphomas, targeting the MMP3/TNF α -mediated migration of stromal cells in the B cell follicle may have great potential as a future therapeutic modality against aberrant GC-associated disorders.